1999
DOI: 10.1523/jneurosci.19-24-j0001.1999
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Persistent Tetrodotoxin-Resistant Sodium Current In SNS-Null And Wild-Type Small Primary Sensory Neurons

Abstract: TTX-resistant (TTX-R) sodium currents are preferentially expressed in small C-type dorsal root ganglion (DRG) neurons, which include nociceptive neurons. Two mRNAs that are predicted to encode TTX-R sodium channels, SNS and NaN, are preferentially expressed in C-type DRG cells. To determine whether there are multiple TTX-R currents in these cells, we used patch-clamp recordings to study sodium currents in SNS-null mice and found a novel persistent voltage-dependent sodium current in small DRG neurons of both S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
380
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 417 publications
(425 citation statements)
references
References 25 publications
38
380
2
1
Order By: Relevance
“…As observed for Na v 1.8 mRNA, this was localized primarily over small to medium sized neurons representing 59.0% of all neurons analyzed, while only 13.9% of the neurons analyzed were large size neurons that express detectable levels of this message ( Figure 3; Table 2). These findings are consistent with those previously described (Black et al, 1996;Cummins et al, 1999;Dib-Hajj et al, 1999).…”
Section: Nt-3 Significantly Attenuates Neuronal Na V 18 Mrna Expressionsupporting
confidence: 94%
See 2 more Smart Citations
“…As observed for Na v 1.8 mRNA, this was localized primarily over small to medium sized neurons representing 59.0% of all neurons analyzed, while only 13.9% of the neurons analyzed were large size neurons that express detectable levels of this message ( Figure 3; Table 2). These findings are consistent with those previously described (Black et al, 1996;Cummins et al, 1999;Dib-Hajj et al, 1999).…”
Section: Nt-3 Significantly Attenuates Neuronal Na V 18 Mrna Expressionsupporting
confidence: 94%
“…Consistent with previous reports (Akopian et al, 1996;Black et al, 1996;Cummins et al, 1999;Dib-Hajj et al, 1999), we found that expression is observed primarily in small to medium sized (<35 μm in diameter) neurons. These neurons represent 60.7% of all neurons analyzed, while only 9.6% were larger sized (>35 μm in diameter) neurons (Table 1).…”
Section: Nt-3 Significantly Attenuates Neuronal Na V 18 Mrna Expressionsupporting
confidence: 93%
See 1 more Smart Citation
“…The effect of FHF1B interaction with Na v 1.9 has yet to be determined. Na v 1.8 is a sensory neuron-specific sodium channel that produces a TTX-R current with different kinetic properties compared with Na v 1.5 and Na v 1.9 (42)(43)(44). Although Na v 1.5 and Na v 1.8 share ϳ80% amino acid identity in the CR1ϩCR2 region, Na v 1.8 failed to interact with FHF1B ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased I h could therefore contribute to spontaneous firing (Akasu et al, 1993), but its NGF dependence is unknown. A TTXR-persistent current in DRG neurons, activated around E m or at more hyperpolarized potentials, also tends to depolarize the membrane (Cummins et al, 1999). The NaN Na ϩ channel subunit, thought to be responsible for this current, is upregulated in DRG neurons in NGFoverexpressing mice (Fjell et al, 1999b) and thus may also be upregulated during inflammation.…”
Section: Possible Ionic Mechanismsmentioning
confidence: 99%